Elaboração de geleia de erva-mate (Ilex paraguariensis) - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The Yerba mate (Ilex paraguariensis), typical of subtropical and temperate regions is used in beverage production through its leaves and branches. The raw material and the processing steps are essential to obtain a product with desirable quality, because any change may compromise the final product. Once life expectancy increases every year, natural antioxidants have been used replacing the synthetic ones. Jams stand out in the industry as the second product in commercial importance. It is easy to manufacture, adds value to fruits and it also allows the conservation of these for an prolonged period of time. So, this study aimed to develop jams with different concentrations of yerba mate’s extract, (G1= 40:60% Extract/Base; G2= 50:50% Extract: Base e G3= 60:40% Extract: Base), to evaluate their physic-chemical and sensory characteristics, even as the antioxidant capacity and the content of phenols in them. There were measured physical and chemical determinations of pH, total soluble solids (TSS), total titratable acidity (TTA) and antioxidant activity. A sensory evaluation of jam was performed, using a structured hedonic scale from 1 (extremely dislike) to 9 (extremely like) points, 50 untrained judges rated the attributes appearance, smell, texture and flavor. The content of total phenolic compounds of yerba mate, aqueous extracts and formulations G1, G2 and G3, showed values of 2742.50, 2715.06, 2494.23, 2397.13 and 2120.83 mg gallic acid.100g-¹ sample respectively and antioxidant activity (96.40, 97.38 e 95.96% of inhibition of DPPH). The results of sensory evaluation showed averages of G1= 76, G2= 81 e G3= 78% in the affective acceptance test and G1= 67, G2= 80 e G3= 76% for the purchase intent of jam. So, developed jams exhibit specific characteristics specific and within the norms of current legislation features. The average index of acceptability was higher than 78%, demonstrating that yerba mate has good potential for the development of gel with antioxidant properties.
Keywords: Antioxidante; Compostos fenólicos; Maçã; Geleia de frutas; Avaliação sensorial; Antioxidant; Phenolic compounds; Apple; Fruit jam; Sensory evaluation; CNPQ::CIENCIAS AGRARIAS